Newly bred Matoke banana for Tanzania - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
“Matooke” are an important staple crop in the Highlands of East Africa. They provide food security for nearly 2.5 mio households. Uganda and Tanzania are respectively the first and second producer. These bananas are harvested when still green and then steamed or boiled, and sometimes mashed before consumption. Currently, farmers’ average productivity is around 7 t/ha/year. These low yields are due too many pests and diseases. In 2021 four matooke hybrids were released in Tanzania and this video shows farmers in the Kagera region cultivating these matooke hybrids with yields ranging from 18 to 35 t/ha/year due to resistance to black Sigatoka leaf disease and banana weevils. These new matooke hybrids were developed by the International Institute of Tropical Agriculture (IITA) and the National Agriculture Research Organization (NARO) of Uganda and named NARITAs. They were later tested in Tanzania during 5 years by the Tanzania Agriculture Research Institute (TARI) and its partners.